Clinical significance of hyperhomocysteinemia in infective endocarditis: A case–control study. Issue 39 (September 2016) - Iossa, Domenico; Molaro, Rosa; Andini, Roberto; Parrella, Antonio; Ursi, Maria Paola; Mattucci, Irene; De Vincentiis, Lucia; Dialetto, Giovanni; Utili, Riccardo; Durante-Mangoni, Emanuele
Abstract : Abstract: Blood coagulation plays a key role in the pathogenesis of infective endocarditis (IE). Conditions associated with thrombophilia could enhance IE vegetation formation and promote embolic complications. In this study, we assessed prevalence, correlates, and clinical consequences of hyper-homocysteinemia (h-Hcy) in IE. Homocysteine (Hcy) plasma levels were studied in 246 IE patients and 258 valvular heart disease (VHD) patients, as well as in 106 healthy controls. IE patients showed Hcy levels comparable to VHD patients (14.9 [3–81] vs 16 [5–50] μmol/L, respectively; P = 0.08). H-Hcy was observed in 48.8% of IE patients and 55.8% of VHD ( P = 0.13). Vegetation size and major embolic complications were not related to Hcy levels. IE patients with h-Hcy had a higher prevalence of chronic kidney disease and a higher 1-year mortality (19.6% vs 9.9% in those without h-Hcy; OR 2.21 [1.00–4.89], P = 0.05). However, at logistic regression analysis, h-Hcy was not an independent predictor of 1-year mortality (OR 1.87 [95% CI 0.8–4.2]; P = 0.13). Our data suggest h-Hcy in IE is common, is related to a worse renal function, and may be a marker of cardiac dysfunction rather than infection. H-Hcy does not appear to favor IE vegetation formation or its symptomatic embolic complications.